2008
DOI: 10.1158/0008-5472.can-08-3633
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid Precursor Protein Is a Primary Androgen Target Gene That Promotes Prostate Cancer Growth

Abstract: Androgen receptor (AR) is a critical transcription factor that regulates various target genes and contributes to the pathophysiology of prostate cancer hormone dependently. Here, we identify amyloid precursor protein (APP) as a primary androgen target through chromatin immunoprecipitation (ChIP) combined with genome tiling array analysis (ChIPchip). ChIP-treated DNA were obtained from prostate cancer LNCaP cells with R1881 or vehicle treatment using AR or acetylated histone H3 antibodies. Ligand-dependent AR b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
115
0
7

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(127 citation statements)
references
References 27 publications
5
115
0
7
Order By: Relevance
“…Gain-of-function studies showed that APP overexpression leads to increased cellular proliferation (12,17,42). Lossof-function studies either by APP knockdown (14,16,17) or blockage of sAPP function by antibody application (15) demonstrated regression of carcinoma growth in vitro and in vivo. Such a functional relationship between APP expression and proliferation demonstrates the importance of APP in the pathogenesis of cancer.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Gain-of-function studies showed that APP overexpression leads to increased cellular proliferation (12,17,42). Lossof-function studies either by APP knockdown (14,16,17) or blockage of sAPP function by antibody application (15) demonstrated regression of carcinoma growth in vitro and in vivo. Such a functional relationship between APP expression and proliferation demonstrates the importance of APP in the pathogenesis of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The extracellular domain interacts with matrix proteins and heparan sulfate proteoglycans reflecting its role in migration, adhesion, and cell-matrix and cell-cell interactions (45)(46)(47)(48). Recently, it has been shown that APP is up-regulated in several cancer species, including pancreatic (15), colon (14), melanoma (49), and prostate cancer (17), as well as oral squamous cell carcinoma (15), and has growth-promoting features. Different kinds of stimuli can enhance APP expression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our group and others have identified novel androgen target genes that regulate androgen-dependent tumor growth by performing chromatin immunoprecipitation coupled with tiling array (ChIP-chip) analyses. [8][9][10] Integrative transcriptome sequencing in prostate cancer cells could detect gene fusions, 11 including known prostate cancer-specific rearrangements TMPRSS2-ERG/ETV1. 12 Recently, miRNA profiling has been reported to be informative and predictive in some malignancies, including prostate cancer.…”
Section: Introductionmentioning
confidence: 99%